Illicit Waste Trafficking and Loopholes in the European and Italian Legislation - Morganti, Margaux (European journal on criminal policy and research, 2020)
Evidence shows that waste crimes, principally trafficking, are facilitated by unclear regulatory frameworks. Indeed, lax legislation can unintentionally generate crime opportunities. The aim of this study is to combine criminological and legal knowledge to identify loopholes in the waste regulatory frameworks of the European Union and Italian government. A crime proofing analysis was conducted to identify vulnerabilities in the selected waste legislation. Results indicate the existence of three macrocategories of loopholes: the legal framework, the supply chain, and the justice response system. Policy implications involve the necessity to simplify the language in waste legislation, to create effective measures via which to improve the traceability of waste, and to provide law enforcement authorities with adequate training and technological resources to perform inspection activities. Given the transnational nature of illicit waste trafficking, international cooperation is integral for fighting this crime type.